2013
DOI: 10.1002/term.1817
|View full text |Cite
|
Sign up to set email alerts
|

On the use of dexamethasone-loaded liposomes to induce the osteogenic differentiation of human mesenchymal stem cells

Abstract: Stem cells have received considerable attention by the scientific community because of their potential for tissue engineering and regenerative medicine. The most frequently used method to promote their differentiation is supplementation of the in vitro culture medium with growth/differentiation factors (GDFs). The limitations of that strategy caused by the short half-life of GDFs limit its efficacy in vivo and consequently its clinical use. Thus, the development of new concepts that enable the bioactivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 51 publications
(68 reference statements)
0
25
0
Order By: Relevance
“…SEM images of liposomes (A, adapted from Ref. , with permission from John Wiley & Sons) and polyester NPs (B, adapted from Ref. , with permission from John Wiley & Sons).…”
Section: Types Of Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…SEM images of liposomes (A, adapted from Ref. , with permission from John Wiley & Sons) and polyester NPs (B, adapted from Ref. , with permission from John Wiley & Sons).…”
Section: Types Of Nanoparticlesmentioning
confidence: 99%
“…Such bivalent systems are then able to support cells and also provide growth and differentiation factors . Studies using several types of NPs such as polymeric, liposomes, silica, and calcium phosphate ceramic NPs indicated that the use of nanoparticulate systems as carriers allow a sustained delivery of their cargo. Table summarizes the outcomes of NPs used as drug and gene carriers.…”
Section: Applications For Bone Tementioning
confidence: 99%
See 1 more Smart Citation
“…An adequate combination of signalling molecules should be provided by controlled release systems in order to promote the desired regenerative outcome [112,[157][158][159]. Therefore, liposomes can be used as carriers for the spatio-temporal controlled delivery of GFs, improving stem cell proliferation and differentiation in vitro [160,161].…”
Section: Growth/differentiation Factor Deliverymentioning
confidence: 99%
“…Indeed, the use of these structured biomaterials as delivery devices allows surpassing solubility problems of the therapeutic agents, leading to reduced systemic toxicity and tissue damage . Additionally, they can be designed to protect drugs, peptides, proteins and nucleic acids from premature degradation and undesirable interactions with the biological environment, preserving its bioavailability for longer periods of time . The undesirable side effects in surrounding healthy tissues, due to drug distribution throughout the entire organism, can also be circumvented by delivering therapeutic agents into a specific organ or tissue, using antibodies, peptides or other targeting moieties linked to the surface of the delivery devices …”
Section: Introductionmentioning
confidence: 99%